Petrogenesis of Andesite in Bukitcula, Baleendah District, Southern Bandung, West Java - Asrial, Nouval Muamar; Rosana, Mega Fatimah; Fachrudin, Kurnia Arfiansyah; Nordin, Nazihah (Journal of Geological Sciences and Applied Geology, 2019)
Administratively, Bukitcula Lava located in the area of Baleendah, Southern Bandung, West Java . Geographically located at Longitude 107o36'00" to 107o39'00" and Latitude 7o00'00" to 7o02'42". Baleendah Lava Complex consisted of steeply hill composed by andesite. Petrology, petrography and geochemical studies (XRF analysis) were used to understand the detail of rock characteristics. Petrological analysis studies shows mineral abundances of feldspar, amphiboles, pyroxenes and opaque mineral. Petrographical analysis show abundances of plagioclase, pyroxene, hornblende, and groundmass composed by plagioclase microlites, volcanic glass, and opaque mineral. Texture found in petrography analysis shows glomeroporphyritic, sieve, pyroxene penetration twin, zoning, and trachytic. Based on geochemical analysis, Bukitcula Lava composed by basaltic andesite and andesite according to TAS diagram. The magmatic series of rocks is Calc-Alkali and Tholeiitic series, with High-K and Medium-K (Calc-Alkaline Series) magma group. Magma interract with continental crust, with tectonical setting related on Island Arc Calc-Alkaline Basalt, and origin of magma ranged ranged from ± 139 km - ± 148 km in the Benioff zone. We conclude that the forming of Baleendah Lava Complex was influenced by fractional crystalization and slightly magma mixing.